Smokeless Tobacco and Public Health in Bangladesh - Huque, Rumana (Indian J Public Health, 2017)
Despite the high prevalence of smokeless tobacco (SLT) use among adults in Bangladesh, SLT was not included in the Tobacco Control Law till 2013. Information on SLT use among Bangladeshi people is inadequate for policymaking and implementing effective control measures. With the aim to identify the prevalence and trends of different SLT products, health and economic impacts, manufacture, and sale of and policies related to SLT in Bangladesh, we carried out a literature review, which involved literature search, data extraction, and synthesis. Evidence suggests that in Bangladesh, SLTs range from unprocessed to processed or manufactured products including Sada Pata, Zarda, Gul, and Khoinee. Over 27% of Bangladeshi adults aged 15 years and older use SLT in one form or other. SLT use is associated with age, sex, education, and socioeconomic status. SLT consumption has reportedly been associated with increased prevalence of heart diseases, stroke, and oral cancer and led to around 320,000 disability adjusted life years lost in Bangladesh in 2010. No cessation service is available for SLT users in public facilities. Compared to cigarettes, taxation on SLT remains low in Bangladesh. The amendment made in Tobacco Control Law in 2013 requires graphic health warnings to cover 50% of SLT packaging, ban on advertisement of SLT products, and restriction to sale to minors. However, implementation of the law is weak. As the use of SLT is culturally accepted in Bangladesh, culturally appropriate public awareness program is required to curb SLT use along with increased tax and cessation services.